2015
DOI: 10.1155/2015/153829
|View full text |Cite
|
Sign up to set email alerts
|

Differential Telomere Shortening in Blood versus Arteries in an Animal Model of Type 2 Diabetes

Abstract: Vascular dysfunction is an early feature of diabetic vascular disease, due to increased oxidative stress and reduced nitric oxide (NO) bioavailability. This can lead to endothelial cell senescence and clinical complications such as stroke. Cells can become senescent by shortened telomeres and oxidative stress is known to accelerate telomere attrition. Sirtuin 1 (SIRT1) has been linked to vascular health by upregulating endothelial nitric oxide synthase (eNOS), suppressing oxidative stress, and attenuating telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This is also important as a recent cross-sectional study demonstrated that telomere length is independently associated with subclinical atherosclerosis in subjects with T2D ( 152 ). However, accelerated telomere attrition was recently reported in circulating leukocytes, but not arteries, in T2D compared to control rats ( 156 ). This indicates the importance of immune senescence in diabetic vascular dysfunction/aging pathogenesis and that leukocytes may be primary targets of accelerated aging.…”
Section: Accelerated Vascular Aging In Diabetesmentioning
confidence: 95%
“…This is also important as a recent cross-sectional study demonstrated that telomere length is independently associated with subclinical atherosclerosis in subjects with T2D ( 152 ). However, accelerated telomere attrition was recently reported in circulating leukocytes, but not arteries, in T2D compared to control rats ( 156 ). This indicates the importance of immune senescence in diabetic vascular dysfunction/aging pathogenesis and that leukocytes may be primary targets of accelerated aging.…”
Section: Accelerated Vascular Aging In Diabetesmentioning
confidence: 95%
“…eNOS, endothelial nitric oxide synthase. a reduction in the cellular redox status and an increase in oxidant stress may work together to reduce vascular SIRT1 expression (24)(25)(26). Furthermore, eNOS expression levels have also been shown to be low within cerebral arteries, which implies a connection between SIRT1 and eNOS (27).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblotting was performed in lysates from pooled cerebral arteries (basilar artery, anterior, and posterior communicating arteries). Protein expression of eNOS‐P and total eNOS was measured as previously described (Tajbakhsh et al, 2015 ). The primary antibodies were mouse anti‐eNOS monocloncal primary antibody (BD Transduction Labs, 610296 at 1:1000 dilution) or rabbit anti‐eNOS‐P polyclonal primary antibody (Cell Signaling Technology, 9571 at 1:400 dilution).…”
Section: Methodsmentioning
confidence: 99%